Fungal colonisation on wood surfaces weathered at diverse climatic conditions - Poohphajai, Faksawat; Myronycheva, Olena; Karlsson, Olov; Belt, Tiina; Rautkari, Lauri; Sandak, Jakub; Gubenšek, Ana; Zalar, Polona; Gunde-Cimerman, Nina; Sandak, Anna (Heliyon, 2023)
Natural weathering test at two different European climatic zones were conducted to investigate simultaneously both, the fungal colonisation and weathering process of Scots pine wood (Pinus sylvestris L.). The hypothesis was that the wood performing differently in various climate conditions might affect fungal infestation. The colour changes, wettability, and glossiness were measured as indicators of weathering progress of wood together with an assessment of fungal diversity. Different intensities in weathering, occupancy, and colonisation of fungi on wooden surface were detected. A higher number of fungal species was found on wood exposed to the warm temperate climates compared to subarctic or boreal climates. The dominant fungal species in both locations were from the genera Cladosporium and Aureobasidium. Validerad;2023;Nivå 2;2023-08-15 (hanlid); Funder: Ministry of Education, Science and Sport (MIZS), Slovenia Fingerprinting of Microbial Communities on Contaminated Wooden Surfaces for Further Identification and Differentiation of Fungal Species and Strains InnoRenew